The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.pediatrneurol.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cerebral Palsy With Other Disabilities in Children With Perinatal Arterial Ischemic Stroke

Abstract: The association of cerebral palsy with other disability in children with perinatal stroke has not been well-studied. We examined this association in 111 children with perinatal stroke, 67 with neonatal presentation and 44 with delayed presentation. Seventy-six children (68%) had cerebral palsy, which was hemiplegic in 66 and tri-or quadriplegic in 10. Fifty-five (72%) of the children with cerebral palsy had at least one other disability: 45 (59%) had cognitive/speech impairment which was moderate-severe in 20,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 8 publications
2
29
0
1
Order By: Relevance
“…Other studies found CP in 26% to 68%. 5,6,32,33 Different motor outcomes between studies can be explained by differences in functional measures, follow-up duration (patients with milder motor impairment might been missed), and methodological aspects (studies including only NAIS show motor problems less often than studies including PPIS because, by definition, this group frequently presents with motor problems). About one-third of patients showed delayed mental performance at the 2-year follow-up, in accordance with previous research, 34 but this proportion should not be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found CP in 26% to 68%. 5,6,32,33 Different motor outcomes between studies can be explained by differences in functional measures, follow-up duration (patients with milder motor impairment might been missed), and methodological aspects (studies including only NAIS show motor problems less often than studies including PPIS because, by definition, this group frequently presents with motor problems). About one-third of patients showed delayed mental performance at the 2-year follow-up, in accordance with previous research, 34 but this proportion should not be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, 42% of children did not have a diagnosis of CP and 19% had no neurological diagnosis. Because the Victorian Cerebral Palsy Register requires confirmation of the diagnosis of CP at 5 years of age, our study would have excluded children with subtle or no hemiplegia, and these children are thought to be at lower risk of epilepsy 15 . Furthermore, it is very likely that the longer follow‐up in our study allowed the detection of a greater proportion of incident cases of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In our own cohort of term neonates with perinatal arterial ischemic stroke, among children who presented with stroke in the neonatal period, 54% had cerebral palsy and 22% had moderate-severe cognitive impairment [1]. Approximately 67% of this cohort had childhood epilepsy, though almost a third of those children were able to be weaned off medication during the period that we followed them [22].…”
Section: Discussionmentioning
confidence: 97%
“…Mild epilepsy was defined as less than or equal to one seizure per month while on medication, while moderate-severe epilepsy was defined as more than one seizure per month while on medication. These outcome definitions have been used in previously reported work [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation